Rapid Synthesis of Superabsorbent Smart-Swelling Bacterial Cellulose/Acrylamide-Based Hydrogels for Drug Delivery - Manisha Pandey; Mohd Cairul Iqbal Mohd Amin; Naveed Ahmad; Muhammad Mustafa Abeer (International Journal of Polymer Science)
This study evaluated the effect of solubilized and dispersed bacterial cellulose (BC) on the physicochemical characteristics and drug release profile of hydrogels synthesized using biopolymers. Superabsorbent hydrogels were synthesized by graft polymerization of acrylamide on BC solubilized in an NaOH/urea solvent system and on dispersed BC by using N,N′-methylenebisacrylamide as a crosslinker under microwave irradiation. Fourier transform infrared spectroscopy analysis of the resulting hydrogels confirmed the grafting, and an X-ray diffraction pattern showed a decrease in the crystallinity of BC after the grafting process. The hydrogels exhibited pH and ionic responsive swelling behavior, with hydrogels prepared using solubilized BC (SH) having higher swelling ratios. Furthermore, compared to the hydrogels synthesized using dispersed BC, the hydrogels synthesized using solubilized BC showed higher porosity, drug loading efficiency, and release. These results suggest the superiority of the hydrogels prepared using solubilized BC and that they should be explored further for oral drug delivery.